Association between lifestyle-related factors and low back pain: Evidence from a Japanese population-based study. - Soya Kawabata; Noriaki Kurita; Takuya Nikaido; Ryoji Tominaga; Yuji Endo; Nobuyuki Fujita; Shin-Ichi Konno; Seiji Ohtori (PLoS ONE, 2025)
Low back pain (LBP) is a major public health issue, and lifestyle-related factors (LRFs) are increasingly recognized as key contributors to LBP. However, comprehensive studies using recent data concerning the association between LBP and LRFs remain limited. In this study, a nationally representative sample of Japanese adults were surveyed to evaluate the relationship between LRFs and LBP and to explore how these factors relate to both the severity and chronicity of LBP. A cross-sectional nationwide survey was conducted among 5000 randomly selected Japanese adults aged 20-90 years; valid responses were obtained from 2188. Participants were analyzed using three different methods: (1) those with or without current LBP, (2) those with no/mild or moderate/severe pain, and (3) those with or without chronic LBP. Key LRFs included body mass index, alcohol consumption, smoking, exercise habits, comorbidities (dyslipidemia, diabetes, and hypertension), and self-image regarding body shape. Multivariable logistic regression analysis revealed that current LBP was significantly associated with body mass index (odds ratio [OR]=1.04, 95% confidence interval [CI]: 1.00-1.07), alcohol consumption (OR=1.37, 95% CI: 1.04-1.80), smoking (OR=1.63, 95% CI: 1.21-2.20), and dyslipidemia (OR=1.51, 95% CI: 1.06-2.13), and the severity of LBP was associated with smoking (OR=1.77, 95% CI: 1.19-2.64), lack of exercise (OR=1.55, 95% CI: 1.10-2.15), and dyslipidemia (OR=1.64, 95% CI: 1.06-2.55). In addition, smoking was the only LRF significantly associated with chronic LBP (OR=1.70, 95% CI: 1.23-2.34). Multiple LRFs are associated with the prevalence of LBP. Stratified analysis provided deeper insight into specific risk factors for LBP. In particular, dyslipidemia is linked to pain severity, whereas smoking is associated with both severity and chronicity. Future longitudinal studies should focus on the influence of these key LRFs on onset, severity, and chronicity of LBP.